Intelligence Strategy Using Collection Methods for Narcotics Crime Suspects - Baron, Pangeran; Puspitasari, Maria; Riyanta, Stanislaus (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This article describes the intelligence strategy for identifying drug trafficking networks in the community and the factors that influence the success of conditioning suspected drug offenders in the fight against drugs. This research is based on Article 3 in the State Intelligence Law (UUIN) Number: 17/2011 on the conditioning function. Narcotics crime is a victimless crime because the perpetrator of the crime is also the victim of the crime itself. The problem examined in this study is how the intelligence strategy in identifying drug abuse in the community using Structure Network Analytics and what factors affect the success of conditioning suspected drug crimes. The purpose of this study is to explain the function of conditioning intelligence to conduct Reverse Operations against efforts to eradicate narcotics crimes. This research is expected to be an input and reference in the development of intelligence discipline studies that have similar discussions and can be a reference for state administrators who form laws and involve civil society components that have intersections with intelligence with all its activities to achieve national stability to strengthen the concept of National Resilience.